Publications about education in Mexico in the XIX century - Aguilar, Morelos Torres (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
The article is a product of a research about thirty three newspapers and magazines appeared between 1829 and 1897 in eleven states of the Republic of Mexico , as well as in the city of Mexico, in which the topic of the education is tackled. Its main objective is to analyze, to understand, to compare and to interpret, from the publishing lines, the educational discourse given in the mentioned printed means. The research is relevant because it contributes to offer a finished knowledge on the existing relations between intellectuals, teachers and journalists during the period and on the main pedagogical ideas that all of them defended. The method consisted of the review and analysis of press clipplings of the epoch, the first step was the reading of more than 500 printed ways, to do later a selection of those related to the education. As soon as the universe of educational publications was selected, there was adopted the strategy of using a hermeneutic approach, in order to led the analysis towards the comprehension and the interpretation of the historical process of publication of the described means. The investigation concludes that there were four big tendencies in the educational discourse of the analyzed publications, from the public whom they were addressed: It also concludes that there was printed media that proposed a theoretical discussion of nature, while others were operated in a pragmatic or functional way.